Supply chain management and logistics in emerging markets : selected papers from the 2018 MIT SCALE Latin America Conference - MIT SCALE Latin American Conference on logistics and supply chain management (2016 : Cambridge, Mass.); Yoshizaki, Hugo Tsugunobu Yoshida; Velázquez-Martínez, Josué Cuauhtémoc; Mejia-Argueta, Christopher (Bingley, U.K. : Emerald Publishing Limited, 2020)
In April 2018 more than 150 researchers from 16 different countries convened at MIT for the second SCALE Latin American Conference on Supply Chain Management and Logistics (SCM&L). This edited book presents 18 papers on SCML in Latin America which emerged from this conference. As a region with more than 640 million people, and an economy that grows faster than those of developed regions, Latin America is the subject of large infrastructure projects and heightened interest from multinational companies. With contributors spanning eleven different countries, and comprising MIT faculty and researchers, and academics from prestigious Latin American institutions, this collection covers a variety of relevant topics in SCM&L for the region, and also addresses its lack of cases and applied examples. With cases from Argentina, Ecuador, Mexico, and Paraguay, this book breaks fresh ground by looking at risk analysis, and small firms supply chain management. Making a solid contribution to the regional needs for SCM&L literature for education, research, and practice, this book is relevant to researchers and professionals living and operating in the region, as well as in developing economies beyond.
Chapter 1: Introduction -- Chapter 2: The impact of environmental risks in Supply Chain Resilience; Camil Martinez, John Patrick Paraskevas, Curt Grimm, Thomas Corsi, Sandor Boyson -- Chapter 3: NGOs supplier selection and procurement cost reduction with multidimensional auctions; Joice Ribeiro, Irineu de Brito Jr and Hugo Yoshizaki -- Chapter 4: A collaborative assessment of promotions performance using financial KPIs.; Jorge Garcia, Ana Maria Castañeda, Andres Cardenas, Juan David Suarez, Daniel Prato -- Chapter 5: A hierarchical analysis approach to assess packaging supply chain issues; Alicia Pérez, José Villena, Diego Matuk, Ana Luna and Mario Chong -- Chapter 6: Data-Driven Solutions for Evaluating and Planning Last Mile Operations in Latin America. A Methodological Approach Focused in Quito, Ecuador; Bernardo Puente, Clara Orellana, Carlos Suárez -- Chapter 7: Identifying underlying Urban Logistics factors in Old Downtown of Córdoba, Argentina; Gerardo Heckmann, David Hidalgo -- Chapter 8: Risk Analysis of Transporting Goods by Road in Brazil; Luiz Barreto Silva, Alessandro Silva, Reginaldo Ferreira Chapter 9 . Daily Train Scheduling in Seaport Terminal: a MILP approach; Lucas Guedes, Allan Bretas, Carlos Faria, Bruno Medeiros, Breno Moreira -- Chapter 10: Supply Chain Management for Micro and Small Firms in Latin America; Josué Velázquez, Cansu Tayaksi -- Chapter 11: Collaborative Inventory Replenishment: Discussions and Insights of a Cost-effective Alternative for Non-competitive Small and Medium-sized Enterprises; Carlos Otero, René Amaya, Jairo Montoya, Miguel Jaller -- Chapter 12: Adoption of Best Business and Supply Chain Practices and Micro/Small Firms Performance: Evidence from Northern Peru; Brenda Silupu, Marcos Agurto, Gianmarco Merino, Jennifer Uchofen, Josué Velazquez -- Chapter 13: Managers' knowledge of Key Performance Indicators in Small and Medium Enterprises: wood and timber SMEs in Peru; Jenny Yalico, Maria Ortiz, José Larco, A
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Business logistics -- Latin America -- Congresses; Business & Economics, Infrastructure; Purchasing & supply management